2016
DOI: 10.1371/journal.pone.0152121
|View full text |Cite
|
Sign up to set email alerts
|

Acting like a Tough Guy: Violent-Sexist Video Games, Identification with Game Characters, Masculine Beliefs, & Empathy for Female Violence Victims

Abstract: Empathy—putting oneself in another’s shoes—has been described as the “social glue” that holds society together. This study investigates how exposure to sexist video games can decrease empathy for female violence victims. We hypothesized that playing violent-sexist video games would increase endorsement of masculine beliefs, especially among participants who highly identify with dominant and aggressive male game characters. We also hypothesized that the endorsement of masculine beliefs would reduce empathy towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 40 publications
2
76
0
3
Order By: Relevance
“…As we reported in our original article (Gabbiadini et al 2016; p. 6), post-hoc comparisons indicated that the violentsexist games had higher violence ratings than the violenceonly games. Because it is crucial to disentangle violent content from sexual content, we included the violence ratings as a covariate (for a similar approach, see …”
Section: Video Game Violence As Covariatesupporting
confidence: 60%
See 4 more Smart Citations
“…As we reported in our original article (Gabbiadini et al 2016; p. 6), post-hoc comparisons indicated that the violentsexist games had higher violence ratings than the violenceonly games. Because it is crucial to disentangle violent content from sexual content, we included the violence ratings as a covariate (for a similar approach, see …”
Section: Video Game Violence As Covariatesupporting
confidence: 60%
“…Our work (see Gabbiadini et al 2016) is certainly not the first to suggest that violent sexist video games such as GTA can influence the thoughts, feelings, and behaviors of players. In fact, a scientific consensus is beginning to emerge around the potentially harmful effects of sexist violent video games on players.…”
Section: Is Playing With Sexist Video Games Just Harmless Fun?mentioning
confidence: 85%
See 3 more Smart Citations